ASSESSMENT TO THE PILE BEARING CAPACITY OF INJECTION PILE BASED ON PILE DRIVING ANALYZER AND RE-INJECTION TEST RESULTS (CASE: EASTKAL PENAJAM PROJECT) - Trihanyndio Rendy Satrya; Musta’in Arif (Institut Teknologi Sepuluh Nopember (ITS), 2019)
Injection piling method was used as the main pile driving method at the three warehouses in the Eastkal Penajamproject, Kalimantan, Indonesia. The sub-soil compositions are dominated by clay and sandy soil with very soft to mediumconsistencies. By using injection pile equipment, it is possible to measure the pile bearing capacity from the loading gauge.Since the soil is dominated by clay, the friction capacity overtime will be improved. For that purpose, the piles were re-injectedagain after 3, 10, 11, and 25 days. To establish the forecasting expression of pile bearing capacity enhancement for other piles,non-linear regression analysis was performed. To verify the result, pile driving analyzer (PDA) test for selected piles wascarried out. The results from PDA test were further analyzed by using both direct fields reading in the PDA data logger and theCase Pile Wave Analysis Program (CAPWAP). A linear regression analysis was carried out to complete the blank data due tothe field measurement limitation. In addition to the obtained field data, theoretical analysis of pile bearing capacity with LucianoDecourt method is carried out. From the comparisons of all data, it can be concluded that re-injection pile method provides thehighest safety factor followed by PDA test, CAPWAP analysis, and theoretical design calculation with Luciano Decourt method.